2018
DOI: 10.1037/cep0000122
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between flash based illusory line motion and exogenous visual attention.

Abstract: If a bar suddenly appears between 2 squares after 1 of the squares flashes the bar appears to shoot away from the flashed square toward the other. This occurs despite the bar actually having been presented all at once. This illusory motion is sufficiently strong to cancel real motion drawn in the opposite direction. One explanation for the illusion in these displays is based upon the prior entry benefits generated by exogenous attention at the flashed location. These prior entry benefits can be offset by real … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
37
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(43 citation statements)
references
References 38 publications
(88 reference statements)
6
37
0
Order By: Relevance
“…In addition to ILM area , the cancelation procedure also allows the examination of decision times as a function of distance from the point of subjective equality. Previous studies have shown that decision times are described by a distance decay function (Ha et al, 2018;Hamm, 2017;Han & Hamm, 2018;Han et al, 2016). The tendency for decisions to slow as the condition approaches the point of subjective equality indicates that the illusory and real motion are cancelling and are not consistent with the point of subjective equality reflecting the case in which either the real or the illusory motion is being perceived with equal probability (Hamm, 2017;Han & Hamm, 2018;Han et al, 2016).…”
mentioning
confidence: 95%
See 4 more Smart Citations
“…In addition to ILM area , the cancelation procedure also allows the examination of decision times as a function of distance from the point of subjective equality. Previous studies have shown that decision times are described by a distance decay function (Ha et al, 2018;Hamm, 2017;Han & Hamm, 2018;Han et al, 2016). The tendency for decisions to slow as the condition approaches the point of subjective equality indicates that the illusory and real motion are cancelling and are not consistent with the point of subjective equality reflecting the case in which either the real or the illusory motion is being perceived with equal probability (Hamm, 2017;Han & Hamm, 2018;Han et al, 2016).…”
mentioning
confidence: 95%
“…This general approach will be referred to as the cancelation procedure. Where Steinman et al (1995) utilized PGM-type displays, cancelation of ILM through the use of real motion has been successfully implemented with both flash ILM (Ha, Li, Patten, & Hamm, 2018;Hamm, 2017;Han & Hamm, 2018;Han, Zhu, Corballis, & Hamm, 2016) and TAM (Hamm, 2017). With the direction of ILM being determined by the side of the single stimulus (PGM), the flash ( flash ILM), or the box with the matching attribute (TAM), the cancelation procedure results in a series of measurements over real-motion conditions for left-and right-side inducers.…”
mentioning
confidence: 99%
See 3 more Smart Citations